Drama as an Educational Technology and a Tool for Achieving Personal Educational Results - Rubtsova O.V; Poskakalova T.A; Solov'eva A.G (Moscow State University of Psychology and Education, 2022)
The article focuses on the results of the research project "Adolescent Theater as an Activity Technology for Education and Formation of Personal Educational Results", implemented in 2021-2022 by the Center for Interdisciplinary Research on Contemporary Childhood of the Moscow State University of Psychology and Education. The main goal of the project was to substantiate the the efficiency of school theater as a means of education and a tool for developing meta-subject competences and improving personal educational results in adolescents. For achieving this goal, a unique educational program of drama activities (30 sessions of 45 minutes each) was elaborated and trialed in "Starogorodkovskaya School" in Moscow Region. 10 teenagers aged from 13 to 14 years took part in the project. The research methods included: observation, video recording of drama sessions and subsequent analysis of the videos; analysis of the products of the activity (scripts, short videos, poems); regular interviews with teenagers and teachers, who participated in the project. Several case studies are discussed, demonstrating that drama can become an effective technology for education and development of personal educational results in adolescence.